2016
DOI: 10.1016/j.jmb.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

A Small Number of Residues Can Determine if Linker Histones Are Bound On or Off Dyad in the Chromatosome

Abstract: Linker histones bind to the nucleosome and regulate the structure and function of chromatin. We have previously shown that the globular domains of chicken H5 and Drosophila H1 linker histones bind to the nucleosome with on- or off-dyad modes, respectively. To explore the determinant for the distinct binding modes, we investigated the binding of a mutant globular domain of H5 to the nucleosome. This mutant, termed GH5_pMut, includes substitutions of five globular domain residues of H5 with the corresponding res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 60 publications
(87 reference statements)
3
70
0
2
Order By: Relevance
“…By contrast, the Drosophila GH1 domain (43–46% identical to chicken GH5, Xenopus GH1.0 and human GH1.5; Figure S6A) has been observed to bind off the dyad (Zhou et al, 2013). Moreover, a chicken GH5 mutant could be engineered to adopt an off-dyad binding mode by replacing five surface-exposed residues with the corresponding Drosophila GH1 residue, confirming that GH1 sequence variation can modulate binding mode (Zhou et al, 2016). Interestingly, human GH1.5 matches Drosophila GH1 at two of these mutated positions (Figure S6B), raising the possibility that the H1.5 on-dyad configuration may be less stable than that of the H1.0 isoform.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…By contrast, the Drosophila GH1 domain (43–46% identical to chicken GH5, Xenopus GH1.0 and human GH1.5; Figure S6A) has been observed to bind off the dyad (Zhou et al, 2013). Moreover, a chicken GH5 mutant could be engineered to adopt an off-dyad binding mode by replacing five surface-exposed residues with the corresponding Drosophila GH1 residue, confirming that GH1 sequence variation can modulate binding mode (Zhou et al, 2016). Interestingly, human GH1.5 matches Drosophila GH1 at two of these mutated positions (Figure S6B), raising the possibility that the H1.5 on-dyad configuration may be less stable than that of the H1.0 isoform.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, an NMR study reported an off-dyad binding mode for the Drosophila H1 globular domain (GH1) (Zhou et al, 2013). The different binding modes observed for these two histone isoforms have been ascribed to differences in a few DNA-contacting residues (Zhou et al, 2016). A distinct off-dyad binding mode was reported for human histone H1.4 in the cryo-EM structure of a condensed 12-nucleosome array (Song et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2f,g). The different binding modes were explained by a subsequent study, which identified five key residues in the globular domains of H5 and D. melanogaster H1 that determine the binding location of the globular domain in the chromatosome (on-dyad versus off-dyad binding) 43 , suggesting that a small number of residues in the globular domain of a linker histone variant can determine its binding mode.…”
Section: Roles In Chromatin Organizationmentioning
confidence: 99%
“…This crystal structure is in agreement with previous in vitro experimental data investigating the binding of the H5 globular domain to nucleosomes 41,42 , as well as data showing the binding of the globular domain of mouse H1.0 and its mutants to chromatin in vivo 36 , suggesting that the linker histone binds to the nucleosome in the same way in vitro and in vivo . Using longer linker DNA and full-length linker histone H1.0, it was further shown by NMR and cryo-electron microscopy (cryo-EM) that the tails of the linker histones and the longer linker DNA in the chromatosome do not have a role in determining the binding mode between the nucleosome and the globular domain of the linker histone 43,44 . However, measurements of binding affinity and cryo-EM structural studies showed that within a single chromatosome, the C-terminal tail of H1.0 appears to be preferentially associated with only one of the two available linker DNAs 44,45 , which was speculated to have a role in influencing the assembly and properties of higher-order chromatin structures 44 .…”
Section: Roles In Chromatin Organizationmentioning
confidence: 99%
See 1 more Smart Citation